PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL MANAJER TERHADAP KINERJA KARYAWAN DI KOPERASI KARYAWAN ANGKASA PURA PONTIANAK - Hanisah, Nur; Okianna, Okianna; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the leadership style of transformational managers, employee performance and the influence of transformational leadership style on employee performance in Cooperative Employee Angkasa Pura Pontianak. The research method used is associative research method with two variable that are independent variable and dependent variable The source of this research data is a manager and employees. And the data is through interview to the manager and spread the questionnaire to the employee. the results of the study show that the leadership style of transformational managers in the Employee Cooperative Angkasa Pura Pontianak is very high because it is in the 81% -100% percentage range. And has been evenly averaged with a value of 83.5% percentage. And employee performance good because each indicator has been evenly averaged with a percentage of 80% and is in the 61% -80% percentage range. Based on the results of data processing program SPSS 18 obtained t arithmetic 3.363> t table is 2.018 means the coefficient of leadership style of managers have a significant effect on employee performance. The contribution of R = 0.479 means the influence of the transformational leadership style variable on employee performance of 22.9%.  Keywords: Manager's transformational leadership style, employee performance